A fast nucleic acid extraction system for point-of-care and integration of digital PCR. Issue 23 (25th October 2019) - Yin, Juxin; Hu, Jiumei; Sun, Jingjing; Wang, Ben; Mu, Ying
Abstract : This work showcases a PTFE-based nucleic acid extraction system for point-of-care and integration of digital PCR. Abstract : Digital PCR is a powerful amplification method for absolute quantification of nucleic acids. The systems that integrated the nucleic acid extraction and amplification can reduce detection time, improve accuracy, and reduce labor costs. However, current nucleic acid extraction systems cannot be integrated well with integrated fluidic circuit (IFC) dPCR or droplet digital PCR chips perfectly and limit the application of digital PCR. In this study, a polytetrafluoroethylene (PTFE)-based nucleic acid extraction (PNE) system, which was able to achieve fully closed extraction for micro samples and was able to be integrated with IFC dPCR or droplet digital dPCR (ddPCR) chips perfectly is proposed. For this system, PTFE tubing with an inner diameter of 1 mm was used to load the reagents and superparamagnetic particles (PMPs) were used to extract nucleic acids. The system can extract nucleic acids from cells and blood in 5 minutes. Meanwhile, when nucleic acid extraction was completed, PNE was able to be directly combined with IFC dPCR or ddPCR chips without any intermediate steps. Therefore, the PNE system can realize sample-in-digital-answer-out. It will be highly useful in point-of-care (POC) and promote the development and application of dPCR.